2001
DOI: 10.1063/1.1328736
|View full text |Cite
|
Sign up to set email alerts
|

I. Three-center versus four-center HCl-elimination in photolysis of vinyl chloride at 193 nm: Bimodal rotational distribution of HCl (v⩽7) detected with time-resolved Fourier-transform spectroscopy

Abstract: Three-center versus four-center elimination in photolysis of vinyl fluoride and vinyl bromide at 193 nm: Bimodal rotational distribution of HF and HBr (v5) detected with time-resolved Fourier transform spectroscopy Following photodissociation of vinyl chloride at 193 nm, fully resolved vibration-rotational emission spectra of HCl in the spectral region 2000-3310 cm Ϫ1 are temporally resolved with a step-scan Fourier-transform spectrometer. Under improved resolution and sensitivity, emission from HCl up to vϭ7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 28 publications
2
28
2
Order By: Relevance
“…Martínez-Núñez et al 8,9 employed quasiclassical trajectory ͑QCT͒ calculations to investigate energy partitions of HCl upon photodissociation of CH 2 CHCl at 193 nm and reported that three-center elimination and isomerization of vinylidene to acetylene take place in a concerted, nonsynchronous fashion. In agreement with previous experimental results, 1,7 the four-center elimination produces much vibrationally excited HCl, with a population inversion predicted at =1 ͑Ref. 9͒ or =3 ͑Ref.…”
Section: Internal Energy Of Hcl Upon Photolysis Of 2-chloropropene Atsupporting
confidence: 91%
See 4 more Smart Citations
“…Martínez-Núñez et al 8,9 employed quasiclassical trajectory ͑QCT͒ calculations to investigate energy partitions of HCl upon photodissociation of CH 2 CHCl at 193 nm and reported that three-center elimination and isomerization of vinylidene to acetylene take place in a concerted, nonsynchronous fashion. In agreement with previous experimental results, 1,7 the four-center elimination produces much vibrationally excited HCl, with a population inversion predicted at =1 ͑Ref. 9͒ or =3 ͑Ref.…”
Section: Internal Energy Of Hcl Upon Photolysis Of 2-chloropropene Atsupporting
confidence: 91%
“…Following photodissociation of vinyl chloride at 193 nm, we observed vibration-rotationally resolved emis-sion spectra of HCl ͑ Յ 7͒ with TR-FTS. 1,7 Further work extended to photolysis of vinyl fluoride and vinyl bromide 2 indicated that the HX ͑X = F, Cl, or Br͒ products observed in all vibrational levels show bimodal rotational distributions for which we proposed that the high-J component is associated with production via three-center ͑␣ , ␣͒ molecular elimination and the low-J component with four-center ͑␣ , ␤͒ elimination. Martínez-Núñez et al 8,9 employed quasiclassical trajectory ͑QCT͒ calculations to investigate energy partitions of HCl upon photodissociation of CH 2 CHCl at 193 nm and reported that three-center elimination and isomerization of vinylidene to acetylene take place in a concerted, nonsynchronous fashion.…”
Section: Internal Energy Of Hcl Upon Photolysis Of 2-chloropropene Atmentioning
confidence: 84%
See 3 more Smart Citations